Bangawarra'gumada — Strengthening the Spirit: Causal Modelling of Academic Self-Concept and Patterns of Disengagement for Indigenous and Non-Indigenous Australian Students. Issue 1 (22nd July 2010) - Bodkin-Andrews, Gawaian H.; Dillon, Anthony; Craven, Rhonda G.
Abstract: The notion of academic disengagement, regardless of its specific conceptualisation (e.g., cognitive, affective, or behavioural) is one that has received considerable attention within the educational and social psychological literature, especially with regard to disadvantaged minority groups. Akhough such research has done much to identify the complexity of factors as to why some minority groups may disengage from the schooling system (extending well beyond rightfully maligned deficit models), there is a still a need to empirically identify factors that may lesson the risk of disengagement. This investigation tested the causal impact of secondary students' academic self-concept on patterns of school disengagement (once prior measures of disengagement had been accounted for) for both Indigenous and non-Indigenous Australian secondary students across two time waves of data. The results suggest that a heightened sense of academic self-concept is causally, yet differentially, related to varying patterns of disengagement for both Indigenous and non-Indigenous students. The implications of this research suggest that academic self-concept may be a key variable to unlocking trends of school disengagement that have been noted for Indigenous Australian students, although more effort should be made to increase the strength and importance of academic self-concepts for Indigenous students.